Pengelolaan Program Bimbingan dan Konseling di Sekolah Menengah Atas - Ayi Nazmul Hidayat (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2012)
The training is intended to the coordinator of Guidance and Counselling (BK) for administering relevant programs in actual high school circumstances. The target training is the coordinator of Guidance and Counselling. The methods which are used such as lectures, discussions, and demonstrations/practice.The finding result of this training is the participants transformation, among others: (1) They have an enthusiasm and are capable of creating BK program suitable with the needs and students concern, (2) They feel quite satisfied to join the training and expect other trainings, (3) They capable to uncover the needs and student issues, (4) understand the BK program management system, and (5) Increasing motivation to working out their skills. The final results obtained is how to gain the characteristics of students, manage and create the programs that match the characteristics of BK students so that the BK program could be obtained optimally. Implementing BK management program is recommended and supposed to use these following matters: (1) Adjust to the conditions of their schools, (2) Preparation of BK personnel capabilities is needed, especially in terms of analyzing the needs and students’problem, and (3) Analyse the students needs and problems as references for intensifying other management aspects.